Marketing multicanal como fonte de vantagem competitiva: estudo no setor de varejo de bens de consumo - Morais, Aline Silva Autran de (2017)
The retail sector has substantial economic and social participation in Brazil and Santa Catarina region. It is believed that the strategy of offering customers different sales/service channels (called multichannel marketing) tends to increase customer base, sales volume, and market share. Thus, this study sought to analyze if the multichannel marketing strategy is a source of competitive advantage in the consumer goods retail sector in the Florianópolis/SC region. The study comprehends quantitative, descriptive research, in the form of cross-sectional field survey, and application of self-administered questionnaire, involving 90 retailers. The data collected were analyzed with the assistance of descriptive statistics, cluster analysis, analysis of variance (ANOVA) and multiple regression analysis. The results indicate that the practice of multichannel marketing is recent in the region; that the online channels are the most used; that the strategies most used are customer satisfaction/complaint, visual merchandising, competitive product/brand portfolio, customer loyalty/relationship, and internet/social network monitoring; that there is a statistical difference in the practice of sales promotion, alliances/partnerships, and integration into product and price policies depending on the size of the retailer; that almost all retailers believe that multichannel strategy is valuable to customers. The study also revealed the existence of 4 clusters of multichannel retailers in the region (pioneers, experienced, less experienced, and latecomers), and that the performance of retailers in sales is negatively influenced by customer management, and that performance in market share is positively influenced by the integration of channels and negatively by customer management. The study made it possible to expand the academic knowledge about the relationship between multichannel marketing strategies and competitive advantage, and to obtain empirical data on the practice of integrating channels of retailers of consumer goods.